2018
DOI: 10.3390/ijms19113417
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Nitrogen Level during Seed Production on Wheat Seed Vigor and Seedling Establishment at the Transcriptome Level

Abstract: Nitrogen fertilizer is a critical determinant of grain yield and seed quality in wheat. However, the mechanism of nitrogen level during seed production affecting wheat seed vigor and seedling establishment at the transcriptome level remains unknown. Here, we report that wheat seeds produced under different nitrogen levels (N0, N168, N240, and N300) showed significant differences in seed vigor and seedling establishment. In grain yield and seed vigor, N0 and N240 treatments showed the minimum and maximum, respe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
9
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(10 citation statements)
references
References 44 publications
1
9
0
Order By: Relevance
“…Unlike previous studies [ 8 , 27 , 40 ], our data support a point of view that in the de novo glycerolipid synthesis pathway, the first step is the synthesis of lysophosphatidic acids (LPAs); then, LPAs form phosphatidic acids via the catalytic action of AGPAT . Phosphatidic acids are the precursors for triglyceride biosynthesis.…”
Section: Discussionsupporting
confidence: 67%
See 1 more Smart Citation
“…Unlike previous studies [ 8 , 27 , 40 ], our data support a point of view that in the de novo glycerolipid synthesis pathway, the first step is the synthesis of lysophosphatidic acids (LPAs); then, LPAs form phosphatidic acids via the catalytic action of AGPAT . Phosphatidic acids are the precursors for triglyceride biosynthesis.…”
Section: Discussionsupporting
confidence: 67%
“…Principal component analysis (PCA) was performed using the gene expression profiles. The DESeq R package (1.18.0) (2012) functions were used to estimate size factors, and the nbinom test was used to identify DEGs [ 26 , 27 ]. Fold change ≥2 or ≤0.50, and p -value ≤ 0.05 and were set as the threshold for DEGs.…”
Section: Methodsmentioning
confidence: 99%
“…varying according to genotype and N rate) on seed germination and seed vigour (measured by the accelerated ageing test). Seed germination is a trait strongly determined by the genetic factor (Martínez-Andújar et al, 2012) and is affected by the availability of N (Wen et al, 2018). Seeds acquire vigour throughout the maturation-drying phase in seed development, which not only involves the water loss process but also is considerably dependent on gene expression (Angelovici et al, 2010).…”
Section: Effects Of Te On Seed Physiological Qualitymentioning
confidence: 99%
“…The biological pathways related to NUE are known to be strongly influenced by genetic variation as well as environmental factors such as N availability (Moll et al, 1982;Xu et al, 2012). Studies showed that N limitation can negatively affect wheat growth, morphology, and agronomic traits (Chandna and Ahmad, 2015;Curci et al, 2017;Wen et al, 2018;.…”
Section: Introductionmentioning
confidence: 99%